Influencing Factors of Total Skin Irradiation With Helical Tomotherapy - Wang, Haiyang; Pi, Yifei; Guo, Yuexin; Pei, Xi; Xu, Xie George (Frontiers in Oncology, 2022)
Purpose: To investigate the influencing factors of total skin irradiation (TSI) with helical tomotherapy for guiding the clinical selection of the suitable parameters and optimizing the plan quality and efficiency. Materials and Methods: Six patients with mycosis fungoides who received TSI were retrospectively selected. They all dressed diving suit of 5mm thick as bolus to increase the superficial dose through dose build-up effect. During the planned pretreatment, Ring0, Ring1, Ring2, Ring3, Ring4 of 1cm thick away from the planning target volume (PTV) at a distance of 0cm, 1cm, 2cm, 3cm, 4cm and other normal tissues (NT) were generated. The auxiliary structures were set as the mode of complete block during planning, while the field widths were 5cm and 2.5cm, the pitches were 0.287 and 0.215, the modulation factors were 4 and 3, and the other parameters remained consistent. Results: When the auxiliary structures of complete mode with the distance from the PTV (dPTV) above 3 cm were used, the mean dose, conformity index (CI), and heterogeneity index (HI) of the PTV met the clinical requirements. As dPTV gradually increased, the BOT decreased while the volume of normal tissue received excessive radiation increased. If dPTV was less than 3cm, the clinical requirements were not met. The field widths (FW), pitches, and modulation factors (MF) had no effect on PTVmean and HI. The FW of 2.5cm was slightly better than 5cm for CI. The FW and MF had a significant impact on BOT, which was gradually increasing with the decreasing of the FW and the increasing of the MF. while the pitches had no effect on the BOT. Conclusion: During planning with TSI patients, dPTV is the key factor which has a significant influence on plan quality. We found the plan that dPTV is above 3 cm can meet the clinical requirements. The BOT increases as dPTV increases. The FWs also have an effect on the CI and BOT. it is necessary to comprehensively balance these factors to optimize the quality and efficiency of the plan. We also found that different MFs and pitches have not obvious effect on the results.